Functional connectivity abnormalities in clinical variants of progressive supranuclear palsy - Irene Sintini; Farwa Ali; Yehkyoung Stephens; Heather M. Clark; Julie A. Stierwalt; Mary M. Machulda; Ryota Satoh; Keith A. Josephs; Jennifer L. Whitwell (NeuroImage: Clinical)
Progressive supranuclear palsy (PSP) can present with different clinical variants which show distinct, but partially overlapping, patterns of neurodegeneration and tau deposition in a network of regions including cerebellar dentate, superior cerebellar peduncle, midbrain, thalamus, basal ganglia, and frontal lobe. We sought to determine whether disruptions in functional connectivity within this PSP network measured using resting-state functional MRI (rs-fMRI) differed between PSP-Richardson’s syndrome (PSP-RS) and the cortical and subcortical clinical variants of PSP. Structural MRI and rs-fMRI scans were collected for 36 PSP-RS, 25 PSP-cortical and 34 PSP-subcortical participants who met the Movement Disorder Society PSP clinical criteria. Ninety participants underwent flortaucipir-PET scans. MRIs were processed using CONN Toolbox. Functional connectivity between regions of the PSP network was compared between each PSP group and 83 healthy controls, and between the PSP groups, covarying for age. The effect of flortaucipir uptake and clinical scores on connectivity was assessed. Connectivity was reduced in PSP-RS compared to controls throughout the network, involving cerebellar dentate, midbrain, basal ganglia, thalamus, and frontal regions. Frontal regions showed reduced connectivity to other regions in the network in PSP-cortical, particularly the thalamus, caudate and substantia nigra. Disruptions in connectivity in PSP-subcortical were less pronounced, with the strongest disruption between the pallidum and striatum. There was moderate evidence that elevated subcortical flortaucipir uptake correlated with both increased and reduced connectivity between regions of the PSP network. Lower connectivity within the PSP network correlated with worse performance on clinical tests, including PSP rating scale. Patterns of disrupted functional connectivity revealed both variant-specific and shared disease pathways within the PSP network among PSP clinical variants, providing insight into disease heterogeneity.